ANALISIS DAYA SAING DAN MUTU KOPI DI KECAMATAN SUMBERJAYA KABUPATEN LAMPUNG BARAT - Elisa Ramanda; Dyah Aring Hepiana Lestari (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2016)
This research aims to know the comparativeness and competitiveness of coffee farming and the quality of the coffee beans produced in Sumberjaya Subdistric of West Lampung Regency.The research used a survey method in which respondents were 71coffee farmers. This research was done at Tugusari Village from April-June 2015.  The data was analized by the Policy Analysis Matrix (PAM) and by descriptive analysis using comparation to standard of GMP (Good Manufacturing Practice), namely ICO 407 and SNI 01-2907-2008. The result showed that coffee farming in Sumberjaya Distric had comparative and competitiveness with 0.35 DRCR / DRC and 0.83 PCR.Coffee farming had quality according to GMP in every harvest and post-harvest processes such as picking, sorting, processing, packaging and storage.Key words: comparativeness, competitiveness, and GMP